KONSEP MANAJEMEN KELAS - Rahmawati, Ima; Lestari, Lilis; Setiawan, Waslim (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
The quality of administrative staff performance significantly impacts the smooth operation of school administration. At SMA Negeri 1 Cibungbunglang, it is evident that the administrative staff work very cohesively, and communication between staff and leadership is effective. This study aims to analyze in depth the leadership style of the head of administrative staff in efforts to strengthen and enhance the performance of the administrative staff. The research method used is qualitative with a descriptive approach, employing in-depth interviews with the head of administrative staff and the staff members. The results indicate that the head of administrative staff at SMA Negeri 1 Cibungbulang employs a democratic leadership style.